Chemical composition of oriental spruce (Picea orientalis) and oak (Quercus spp.) barks - Oktay GÖNÜLTAŞ; Mualla BALABAN UÇAR (Turkish Journal of Forestry, 2017)
In this study, the chemical composition of bark from oriental spruce (Picea orientalis), which occur as a result of logging production of forestry enterprises, and oak (Qercus spp.) bark, which are industrial waste of the wood panel industry after board production, were analyzed by wet chemical analysis of wood and analysis methods of phenolic compound. Ash content values of the barks obtained from Artvin and Trabzon area were 4.31% and 3.99%, respectively, while the oak bark samples were 10.02%. Hot water solubility of the spruce bark samples were higher than the oak bark samples. Residual lignin contents of Artvin spruce, Trabzon spruce, and oak were 19.53%, 20.61%, and 18.49%, while α-cellulose contents were 37.28%, 37.92%, and 41.59%, respectively. The results of the total phenol content and butanol-HCl assay showed that Artvin spruce barks had higher values than other bark samples. As hydrolysable tannins, there were gallo tannin in the samples of spruce and oak barks whereas ellagic tannin content has not been determined.